2014
DOI: 10.1080/19368623.2013.813887
|View full text |Cite
|
Sign up to set email alerts
|

Eat to Live or Live to Eat? Mapping Food and Eating Perception of Malaysian Chinese

Abstract: The purpose of this study is to explore the perception of Malaysian Chinese towards food and eating by using a qualitative marketing research tool, known as the Zaltman Metaphor Elicitation Technique. Twelve Malaysian Chinese were asked to collect photographs that represented their thoughts and feelings about food and eating. The results surfaced six broad meanings Malaysian Chinese have about food and eating: (a) health, (b) trying new food, (c) people, (d) home cooked food, (e) enjoyment, (f) happiness. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…Generation Y describe themselves as 'foodies' (33) , with a Gallup poll showing that 57 % of Millennials eat at a quickservice restaurant at least once weekly, compared with 47 % of those aged 40-49 years, 44 % of those aged 50-64 years and 41 % of those aged 65 years or older (34) . While Millennials eat out more often than non-Millennials (3·4 v. 2·8 times per week) (35) , they are a part of the growing trend towards consumers becoming concerned about their health and the healthiness and quality of the foods they eat (36,37) . Therefore, to better understand if restaurant menu labelling affects the calorie intake of college (Generation Y) students, the following two hypotheses were proposed: H1.…”
Section: Generation Y's Healthy Eating Behavioursmentioning
confidence: 99%
“…Generation Y describe themselves as 'foodies' (33) , with a Gallup poll showing that 57 % of Millennials eat at a quickservice restaurant at least once weekly, compared with 47 % of those aged 40-49 years, 44 % of those aged 50-64 years and 41 % of those aged 65 years or older (34) . While Millennials eat out more often than non-Millennials (3·4 v. 2·8 times per week) (35) , they are a part of the growing trend towards consumers becoming concerned about their health and the healthiness and quality of the foods they eat (36,37) . Therefore, to better understand if restaurant menu labelling affects the calorie intake of college (Generation Y) students, the following two hypotheses were proposed: H1.…”
Section: Generation Y's Healthy Eating Behavioursmentioning
confidence: 99%
“…One plausible explanation for this occurrence may be related to the symbolic aspects of food consumption (Kniazeva & Venkatesh, 2007). When food consumption occurs in a setting involving other people, it becomes a key figure in establishing powerful interpersonal relationships (Kemmer, Anderson, & Marshall, 1998;Yang, Khoo-Lattimore, & Lai, 2014). In this role, food becomes a powerful way to connect people (Kniazeva and Venkatesh, 2007).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Past studies documented that health benefits are the main reason behind the consumption of halal food among the non-Muslim consumers, that consist of Chinese and Indian [13]. These benefits are in line with the non-Muslim consumers' consideration and preference to consume safe and fresh ingredients on their daily food intake [14][15][16][17]. Furthermore, past studies also revealed the significant purchasing power among the Malaysian non-Muslim consumers, due to higher monthly income [18][19][20].…”
Section: Introductionmentioning
confidence: 85%